Development of the WHO Caregiver Skills Training Program for Developmental Disorders or Delays - Salomone, Erica; Pacione, Laura; Shire, Stephanie; Brown, Felicity L.; Reichow, Brian; Servili, Chiara (Frontiers in Psychiatry, 2019)
Globally, 52.9 million children under the age of 5 experience a developmental disability, such as sensory impairment, intellectual disability and autism spectrum disorders, and 95% of them live in low-and-middle-income countries. Most of these children lack access to care. In light of the growing evidence that caregivers can learn skills to support their children’s social communication and adaptive behaviour and to reduce challenging behaviour, the World Health Organization developed a novel Caregiver Skills Training Programme (CST) to address this treatment gap. This report outlines the development process, content and global field-testing strategy of this novel caregiver-mediated intervention for families of children with developmental disorders or delay. The CST programme is designed to be feasible, scalable and adaptable and appropriate for implementation in low-resource settings by non-specialists. The programme was informed by an evidence review, utilizing a common elements approach and was developed through extensive stakeholder consultation and an iterative revision process. The programme is intended for a global audience and was designed to be adapted to the cultural, socio-economic, geographic and resource context in which it is used to ensure that it is comprehensible, acceptable, feasible and relevant to target users. It is currently undergoing field-testing in more than 30 countries across all world regions.